Virtual Avatar (VTuber) Design in Creative Education: A Study of the Roles of Aesthetics, Interactivity and Engagement - Yuyun Vitara Trinanda (AMK : Abdi Masyarakat UIKA, 2026)
Advances in digital technology have spurred various innovations in the field of education, one of which is the use of virtual avatars, or Virtual YouTubers (Vtubers), as a creative educational medium. Vtubers serve not only as visual representations of educators but also as a means of interaction capable of enhancing audience engagement in the learning process. This study aims to analyze the role of virtual avatar (Vtuber) design in creative education by examining aspects of aesthetics, interactivity, and audience engagement. This study uses a qualitative method, using a review of the literature already published. Data were collected through an analysis of various journals and scientific publications related to character design, digital learning media, and user interaction within virtual content. The results indicate that the aesthetic design of virtual avatars significantly influences the audience’s initial interest, while interactivity plays a major role in enhancing engagement and sustaining attention during learning. The study’s conclusion affirms that attractive, interactive, and communicative virtual avatar designs can serve as an effective strategy for improving the quality of creative education in the digital age.